PENGUNGKAPAN MODAL INTELEKTUAL: FAKTOR PENENTU DAN KONSEKUENSINYA PADA NILAI PERUSAHAAN - Suaryana, I Gusti Ngurah Agung (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2019)
Intellectual capital is a knowledge-based resource that plays an important role in creating a sustainable competitive advantage of a company. Intellectual capital is an important resource in the era of information and knowledge for company growth. Intellectual capital as an important resource owned by the company needs to be disclosed by the company to investors and potential investors. Disclosure of intellectual capital in Indonesia is still voluntary, it has been implicitly regulated in PSAK No. 19. This research will examine the determinants of intellectual capital disclosures and their consequences on company value. The determining factor that is suspected to affect the disclosure of intellectual capital in Indonesia is the number of board of commissioners, the proportion of independent board of commissioners, company size, and leverage. The consequence of intellectual capital disclosure is the value of the company. The study population was all companies included in the LQ45 on the Indonesia Stock Exchange in the period 2014 to 2016. The number of research samples was 135 observations. The analysis used is multiple linear regression. The results of this study found the number of board of commissioners, the proportion of independent board of commissioners, company size, and leverage had a positive effect on the disclosure of intellectual capital. The broader disclosure of intellectual capital, the higher the value of the company. Keywords : Intellectual Capital Disclosure ; Company Value ; Board of Commissioners ; Company Size